Analysis of salinity stress on biomass yield in ornamental tree species (Current Horticulture, 2024)
An experiment was conducted to study the response of subtropical ornamental tree species to five salinity levels, 0, 3, 4, 5 and 6 dS/m. Salinity effect was evaluated on the basis of changes in biomass under different salinity treatments. Different concentrations of NaCl were applied from May 2015 to October 2015 and different parameters were recorded at the end of October 2015. Aggravated salinity stress caused significant (P
Keywords: Saline water; Fresh weight; Dry weight; Root length; Ornamental trees; Salinity stress; Biomass